The relationship between gadget use and eye health in school-age children at the elementary school of Alun-Alun Kalijati - Manuji, Rosy; Nuraeni, Ade; Handayani, Fitri; Rosiah, Rosiah (Indonesian Nursing Journal, 2024)
Background: Currently, the use of gadgets has increased drastically in all sectors, especially among school-aged children. Improper use of gadgets, such as ignoring time limits, short distances, and the wrong positions, can have an impact on eye health. Unhealthy eyes will affect a child's learning process and can lead to serious eye problems. Purpose: To analyze the relationship between gadget use and eye health in school-age children at the elementary school of Alun-Alun Kalijati. Methods: This research used a descriptive correlational research design, with the approach used in this research being a cross-sectional approach. The sample for this study consisted of 68 students from grades 1 to 6 at Alun-alun Kalijati State Elementary School through stratified random sampling. Results: These findings showed that the majority of respondents often used gadgets; 38 respondents (68%) and 37 respondents (54%) had poor eye health. analysis of the relationship between gadget use and eye health obtained a p-value score of 0.000. Conclusion: It can be concluded that there is a significant relationship between gadget use and eye health in school-aged children at Kalijati Square Elementary School. Schools and parents need to be aware of and initiate rules for using gadgets for students.